10.1142/9789814343060 (CrossRef Listing of Deleted DOIs, 2000)
Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by persistent inflammation and progressive joint damage. This study investigated the role of microRNA-223 (miR-223) in RA and evaluated the therapeutic effects of triptolide (Tri), a diterpenoid epoxide derived from the traditional Chinese medicinal herb Tripterygium wilfordii. A collagen-induced arthritis (CIA) mouse model was used to assess the effects of Tri and methotrexate (MTX). Micro-computed tomography, histological staining, enzyme-linked immunosorbent assay, flow cytometry, RT-qPCR, and western blot analysis were used to evaluate joint damage, inflammation, cytokine profiles, miR-223 expression, and the function of CREBZF, a downstream target of miR-223. CIA mice exhibited marked joint inflammation, swelling, bone erosion, and inflammatory cell infiltration, increased pro-inflammatory cytokine levels, and elevated miR-223 expression. Tri and MTX ameliorated these abnormalities and protected against bone erosion and inflammation. Tri suppressed the disease-associated elevation of miR-223, attenuated pathological fibroblast-like synoviocyte (RA-FLS) phenotypes, and shifted cytokine profiles toward an anti-inflammatory state. Dual-luciferase reporter and AGO2-RIP-qPCR assays supported direct regulation of CREBZF by miR-223. Tri restored CREBZF expression and inhibited NF-κ B signaling, thereby reducing RA-FLS proliferation and promoting apoptosis. These findings indicate that Tri ameliorates RA, at least partly, through the miR-223/CREBZF axis and identify this pathway as a potential therapeutic target.